A EMERGENCY NURSES' EXPERIENCES IN PERFORMING CARDIOPULMONARY RESUSCITATION IN CARDIAC ARREST PATIENTS: A LITERATURE REVIEW - Sumardino, Sumardino; Kahyudin, Bayu Akbar (Nurse and Health: Jurnal Keperawatan, 2025)
Abstract Background: Cardiopulmonary resuscitation (CPR) is the primary lifesaving measure for patients experiencing cardiac arrest, and emergency nurses play a central role in its implementation. Nurses' experience in performing CPR is a critical factor influencing resuscitation quality, clinical decision-making, and patient outcomes. However, this experience is often influenced by various factors such as clinical competence, training availability, psychological well-being, team dynamics, and work environment. Objective: This article aims to identify and analyze the experiences of emergency nurses in performing CPR on cardiac arrest patients based on a literature review of various recent studies. Design: Literature review search using Google Scholar electronic database, Science Direct published in 2020-2025 with search keywords emergency OR Emergency AND Nurse OR Nurse AND CPR OR CPR AND Cardiac Arrest OR Cardiac Arrest. Inclusion Criteria are Journals related to Emergency Nursing Experience &Journals discussing cardiopulmonary resuscitation. Data analysis involved critical appraisal, skimming, and scanning, separating irrelevant articles from relevant ones. Results: There were 6 articles found that were in accordance with the topic, and through review, it was found that they showed that the literature review indicates that emergency nurses' experience in performing cardiopulmonary resuscitation (CPR) on cardiac arrest patients is influenced by a combination of technical skills, psychological preparedness, the work environment, and ongoing training. Conclusion: Emergency nurse experience is a key element in the successful implementation of CPR on cardiac arrest patients. Strengthening the capacity of nurses through education, training, and work environment support is a strategic step to improve the quality of emergency services and patient safety. Keywords: emergency nurses, cardiopulmonary resuscitation, cardiac arrest, clinical experience